2021
DOI: 10.1111/mec.15822
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous genetic basis of age at maturity in salmonid fishes

Abstract: Understanding the genetic basis of repeated evolution of the same phenotype across taxa is a fundamental aim in evolutionary biology and has applications in conservation and management. However, the extent to which interspecific life‐history trait polymorphisms share evolutionary pathways remains underexplored. Here, we address this gap by studying the genetic basis of a key life‐history trait, age at maturity, in four species of Pacific salmonids (genus Oncorhynchus) that exhibit intra‐ and interspecific vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 172 publications
3
38
1
Order By: Relevance
“…Rock1 and Greb1L associated with return timing, and Vgll3 and six6, associated with age at maturity). This is similar to recent findings by (Waters et al, 2021), who did not identify any significant associations between the latter two genes and age at maturity in Coho salmon. Moreover, our study did not focus on variation in life history and phenotypic traits among populations, and therefore we did not investigate similar molecular targets of selection.…”
Section: Partial Parallelism and Subtle Allele Frequency Changesupporting
confidence: 92%
“…Rock1 and Greb1L associated with return timing, and Vgll3 and six6, associated with age at maturity). This is similar to recent findings by (Waters et al, 2021), who did not identify any significant associations between the latter two genes and age at maturity in Coho salmon. Moreover, our study did not focus on variation in life history and phenotypic traits among populations, and therefore we did not investigate similar molecular targets of selection.…”
Section: Partial Parallelism and Subtle Allele Frequency Changesupporting
confidence: 92%
“…The vgll3 gene associated with age at maturity for Atlantic salmon does not appear to influence age at maturity in Chinook, Coho, Sockeye, or Steelhead (Waters et al, 2021 ). The same study showed that the six6 gene is associated with age at maturity in Sockeye and Steelhead, although the effect of the six6 genotype did not differ between sexes in either species (Waters et al, 2021 ). There was no association between the six6 gene and age at maturity in Chinook or Coho.…”
Section: Discussionmentioning
confidence: 99%
“…In species that are threatened or endangered, such as Coho salmon, reduced population growth rates would be detrimental to conservation efforts. While recent work has begun to address sexual conflict in salmonids by uncovering the genetic architecture of age and length at maturity and ARTs in salmonids (Ayllon et al, 2015 ; Barson et al, 2015 ; Pearse et al, 2019 ; Sinclair‐Waters et al, 2020 ), it is clear that species and populations vary in both genetic architecture for these traits and the degree to which that genetic architecture is sex‐specific (Kusche et al, 2017 ; Waters et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has further demonstrated significant associations between six6 and age at maturity in both sockeye salmon and steelhead trout (Waters et al, 2021;Willis et al, 2020).…”
Section: Outlier Loci and Ecotype Identificationmentioning
confidence: 96%